2010
DOI: 10.4000/netcom.481
|View full text |Cite
|
Sign up to set email alerts
|

Urban regeneration, retail development and the role of information and communication technologies

Abstract: The text is a facsimile of the print edition. Studies, NETCOM, vol. 24 (2010) Networks and Communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It has been contended also that ICT can be used as a tool by marketing professionals to analyse the market. For instance, through its various services, such as providing free Wi-Fi in public places or coffee shops, and providing services through mobile phones, ICT can be used to attract people and activities to the central areas, which is an important aspect in revitalising the central areas (De Filippi et al, 2020;Jeong et al, 2010). Similarly, the use of ICT would support the designing of spaces by urban planners, architects, and designers (Lepy, 2008).…”
Section: The Role Of Ict In Placemakingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been contended also that ICT can be used as a tool by marketing professionals to analyse the market. For instance, through its various services, such as providing free Wi-Fi in public places or coffee shops, and providing services through mobile phones, ICT can be used to attract people and activities to the central areas, which is an important aspect in revitalising the central areas (De Filippi et al, 2020;Jeong et al, 2010). Similarly, the use of ICT would support the designing of spaces by urban planners, architects, and designers (Lepy, 2008).…”
Section: The Role Of Ict In Placemakingmentioning
confidence: 99%
“…This strategy is aligned to Component 1, enhancing accessibility and safety, which was found to be the most essential component in revitalisation. This strategy is likely to assist in enhancing economic activities and improve accessibility to different means of transportation as well as improving safety through information on various criminal activities (De Filippi et al, 2020;Jeong et al, 2010).…”
Section: Evaluation Of Ict-linked Strategic Measures To Revitalise the City Centresmentioning
confidence: 99%
“…A US study based on urban planning reports and proposals found that urban renewal projects were expected to achieve new development while preserving old physical and historical values. Urban renewal had been characterised as strengthening the central city, enhancing human interaction, and valuing nature and neighbourhood (Jeong et al, 2010). The characteristics and dilemmas of urban renewal highlight the significance of UUS use.…”
Section: Introductionmentioning
confidence: 99%